Decomposi????o de gastos p??blicos e o impacto no crescimento do consumo em cinco UF???s brasileiras: mobilidade urbana e fun????es de fluxo - Silva, Francisco de Assis da (2016)
This thesis is divided in two main chapters: The first chapter revolves around the decomposing of five Federative Units's expenses, taking in account the revenue of each distinct unit, in healthcare, education and transport and in the search for empirical evidence, supported by a adapted theoretic model, of the impact of the latter in the Consumption Growth Rate of said Federative Units. The data was delated and the econometric estimation of the model parameters was made through a non-linear method. This allowed the derivated model parameters to be calculated and the ascertainment of the influence of transport investiment in the consumption. The second chapter's theme is Urban Mobility, initially discussing the population's necessity of transiting in the urban space, the problematic of traffic jams, the inefficacy of public transportation, and the externalities and diseconomies generated by said factors. In the endeavour of modeling the flow of vehicles through a road network, the so called "Flow Functions" are presented: this family of functions determines the time spent in shuttle between two consecutive bus stations and captures the e effects the increase of users sharing the same route has on the travel time.